2018
DOI: 10.1080/20445911.2018.1553884
|View full text |Cite
|
Sign up to set email alerts
|

Not as gloomy as we thought: reassessing how the public understands probability of precipitation forecasts

Abstract: Prior research asking people to interpret probability of precipitation (PoP) forecasts showed that many of them wrongfully believe that PoP forecasts are derived from a percentage of time, a percentage of a region or the strength of agreement among forecasters. We posit that the wording of PoP interpretation tasks matters, because it is associated with different metacognitive feelings used as cues in situations of uncertainty. We hypothesised that the fluency of the correct PoP interpretation is lower than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, it seems that the probability terminology definition of PoP forecasts has not been consistently and adequately explained, in general, to Spanish students participating in the current study. In this regard, other researchers emphasize the need of promoting the use of probabilistic weather forecasts (see, e.g., Fundel et al 2019;Fleischhut et al 2020) by means of a more fluent and simple view on PoP forecasts interpretation that would help weather forecast users to believe in the quality of the interpretation and its utility (Juanchich and Sirota 2019). In this regard, Handmer and Proudley (2007) showed that the participants in their study generally understood the basic probability concept used in weather forecasts.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…However, it seems that the probability terminology definition of PoP forecasts has not been consistently and adequately explained, in general, to Spanish students participating in the current study. In this regard, other researchers emphasize the need of promoting the use of probabilistic weather forecasts (see, e.g., Fundel et al 2019;Fleischhut et al 2020) by means of a more fluent and simple view on PoP forecasts interpretation that would help weather forecast users to believe in the quality of the interpretation and its utility (Juanchich and Sirota 2019). In this regard, Handmer and Proudley (2007) showed that the participants in their study generally understood the basic probability concept used in weather forecasts.…”
Section: Discussionmentioning
confidence: 91%
“…They found that uncertainty was only expressed for probability of precipitation (PoP) in their study sample, and it was generally conveyed in a percentage format. Additionally, although the use of probabilistic weather forecasts has been widely promoted (see, e.g., National Research Council 2006;Sivle 2016;Fundel et al 2019;Fleischhut et al 2020), Juanchich and Sirota (2019), based on informal observations, also highlighted that it is currently rare to see probabilistic forecasts on British or American TV channels, or contain at best limited information about uncertainty (Morss et al 2008). This issue could produce false certainty in forecasts in the target audience of these weather products, not admitting that forecasts may sometimes fail.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations